Interaction among offset parallel cracks in an orthotropic plane under thermo-mechanical loading - Tanwar A.; Singh R.; Das S.; Altenbach H. (My University, 2025)
The article deals with the problem of three thermally insulated cracks embedded in a fibrous composite material subjected to thermo-mechanical loading. Orthotropy is ensured by the unidirectional reinforcement of fiber. The considered infinite orthotropic plane is divided mathematically into three parts. The present mathematical model comprises of a central crack parallel to two symmetric collinear cracks at an offset distance to it. All the cracks under consideration are thermally insulated and aligned in the fiber direction. Using the Fourier integral transformed technique, the governing equations are reduced into a pair of singular integral equations. The Chebyshev polynomials are used to solve the integral equations of first kind with Cauchy kernel functions. Numerical values of the mode I stress intensity factors (SIFs) at the tips of the cracks are found for different lengths and distance between those. The effect of cracks' interaction on the SIFs is depicted graphically for the fiber-reinforced composite (FRC) material constituted by carbon-based fiber—Graphite and matrix—Epoxy. © 2022 Wiley-VCH GmbH.